Λιμνούλα και πυκνή βλάστηση με αναρριχώμενα φυτά στο παραποτάμιο δάσος του Νέστου - Έγχρωμον Εργαστήρι Φωτογραφίας (1997)
Λιμνούλα και πυκνή βλάστηση με αναρριχώμενα φυτά στο παραποτάμιο δάσος του Νέστου